Ambiguity, nondeterminism and state complexity of finite automata - Han, Yo-Sub; Salomaa, Arto; Salomaa, Kai (Acta Cybernetica, 2017)
The degree of ambiguity counts the number of accepting computations of a nondeterministic finite automaton (NFA) on a given input. Alternatively, the nondeterminism of an NFA can be measured by counting the amount of guessing in a single computation or the number of leaves of the computation tree on a given input. This paper surveys work on the degree of ambiguity and on various nondeterminism measures for finite automata. In particular, we focus on state complexity comparisons between NFAs with quantified ambiguity or nondeterminism.